PERANCANGAN DAN PEMBUATAN WEBSITE INFORMASI KEBUDAYAAN MASYARAKAT SUKU BADUY DI KABUPATEN LEBAK BANTEN - Dhela Tria Afiyanti; Ery Dewayani; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Lack of information media about Baduy Tribe culture makes Baduy Tribe less known by public and there is no special website about Baduy Tribe cultural information to promote Baduy Tribe. The purposes of making this website are to provide information about Baduy Tribe to the community, introducing Baduy Tribe culture to the public by utilizing internet technology such as website, knowing the amount of visitor data, Baduy Tribe products, and cultures of Baduy Tribe.This website is created with System Development Life Cycle (SDLC) method and with programming language PHP, Bootstrap, CSS, and HTML. This website is made with notepad++ as a programming software. Based on the experiments conducted can be concluded that the website can be run and used by the public in finding information about Baduy Tribe